(untitled) (Tanzania Journal for Population studies and Development, 2014)
Adolescents are a rapidly growing group in Tanzania. One out of five Tanzanians are below the age of 19, and a specific concern is their sexual and reproductive health. Although adolescent issues are now featuring high up on the agenda of policy makers and practitioners, little is known about the interactions between adolescents in Tanzania, especially with regard to leisure activities. This article presents findings from a research into social interactions between females and males aged between 15-19 years. The research was conducted in leisure places in the urban neighbourhood of Makurumla Kagera, located in Dar es Salaam, Tanzania. Using a qualitative approach, a total of 20 adolescents were interviewed in a semi-structured style. Findings indicate that leisure places and adolescents’ representations are a controversial topic of discussion in Makurumla Kagera, especially with regard to appropriate female behaviour. This is not merely between generations, but also within the generation itself. A complex mosaic of attitudes and opinions about leisure places and related gender-based representations of adolescents can be observed.